Bionic ceramic armor module and preparation method thereof
By imitating the structural characteristics of the cap teeth, a bionic ceramic armor module is designed, and the combination of ceramic sheets and nano-energy-absorbing colloids is used to solve the brittleness of ceramic materials, improve its resistance and energy absorption density, and achieve lightweight and high efficiency Resist invasion.
Patent Information
- Application Number
- CN202411284659.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-13
AI Technical Summary
Existing ceramic materials have shortcomings in their ability to resist multiple strikes and toughness, and brittleness is its fatal weakness. The existing composite ceramic technology cannot effectively solve this problem.
The design of a bionic ceramic armor module is adopted to imitate the structural characteristics of the cap teeth. Through the N-layer misaligned ceramic bulletproof layer and nano-energy-absorbing adhesive layer, a composite whole that is harmonious with rigidity and flexibility is formed, and the combination of nano-energy-absorbing colloids and ceramic sheets is used. Enhance the ability to resist.
It significantly improves the toughness and energy absorption density of ceramic armor modules, is light in weight, greatly improves the ability to resist penetration during multiple times, and is simple in process and convenient in manufacturing, which is suitable for large-scale production.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of bulletproof armor, and in particular to a bionic ceramic armor module and a preparation method thereof. Background Art
[0002] Ceramic materials have the characteristics of high strength, high hardness, high wear resistance and light weight. They are not only widely used in the protection of tanks, but also in the protection of warships, transport vehicles, aircraft and individual combat. However, brittleness is its fatal weakness and it basically has no ability to resist multiple strikes.
[0003] The ultimate goal of ceramic research in the world is to overcome brittleness and increase toughness, so composite ceramics have become a hot research and development topic. Patent CN103727842A is a fiber / ceramic / metal composite bulletproof plate and its preparation method. It uses a sandwich structure to bond three different materials together with an adhesive, which is a typical structural composite. Patent CN104949581A is a ceramic composite bulletproof chest plate and its preparation method, and patent CN114963874A is a composite bulletproof plate and its preparation method. Both belong to this type of structure. The comprehensive performance has not changed much, and the problems of brittleness and toughness of ceramics cannot be solved.
[0004] Patent CN210533184U discloses a bulletproof plate structure based on bulletproof ceramic sheets. Two layers of ceramic sheets are staggered to avoid the bulletproof defects caused by the overlap. Patent CN111721161A discloses a new bulletproof ceramic unit. Small pieces of ceramic are tightly connected by splicing to improve the ability to resist multiple bullets. The above patents are all improvements in the assembly form of ceramic sheets. Patent CN114853478A discloses a gradient ceramic-based composite material and its preparation method. It composites materials from the source of ceramic preparation to prepare high-temperature resistant composite ceramics, but the actual mechanical properties still do not meet the requirements of bulletproof armor. Patent CN118239793A discloses a micro-laminated gradient ceramic / metal composite material and its preparation method, which belongs to bionic composite ceramics. It has a multi-level micro-laminated gradient structure with soft and hard materials superimposed on each other, and has high strength and high toughness. The ability to resist, but its process is complicated, the yield is low, the cost is high, and it is difficult to effectively and widely promote it. Patent CN117073463A discloses a composite armor with a bionic structure and a method for preparing the same. It makes beneficial explorations into bionic technology based on existing ceramic technology, and imitates the shell-shaped mother-of-pearl organizational structure in the multi-layer stacking of ceramic hemispheres. However, it is only similar in appearance, and in essence fails to fully utilize the super-tough mechanism of ordered stacking, dislocation energy conduction, and nano-energy absorption in the mother-of-pearl structure to solve the problems of brittleness and toughness of ceramics. Summary of the invention
[0005] In view of the technical deficiencies in the existing market, the present invention provides a bionic ceramic armor module and a preparation method thereof, which solves the technical problems that cannot be solved in the prior art. The present invention provides a bionic ceramic armor module and a preparation method thereof. The bionic ceramic armor module of the present invention imitates the constituent elements and structural characteristics of the limpet teeth, which is known as the world's strongest known material, to prepare a bulletproof ceramic armor module that is both rigid and flexible, and essentially solves the brittleness problem of ceramics. The present invention optimizes the structural performance, has good toughness, high energy absorption density, and light weight, and greatly improves its ability to resist multiple penetrations.
[0006] To achieve the above objectives, the present invention is specifically implemented through the following technical solutions:
[0007] A bionic ceramic armor module, characterized in that:
[0008] The bionic ceramic armor module includes N layers of staggered and superimposed ceramic bulletproof layers and nano-energy absorbing adhesive bonding layers. The ceramic bulletproof layer contains M ceramic sheets, which are arranged in an array. The ceramic sheets are tightly bonded by pouring nano-energy absorbing adhesive to form a single thin layer, and the single thin layers are staggered and superimposed in sequence; nano-energy absorbing adhesive is sprayed between the layers of the single thin layer to form a nano-energy absorbing adhesive bonding layer, and the ceramic bulletproof layer and the nano-energy absorbing adhesive bonding layer constitute a composite whole; N is an integer greater than 5; M is an integer greater than 20.
[0009] Preferably, the nano energy-absorbing glue is composited by elastic colloid, oriented nanofibers and energy-absorbing gel; the three components are evenly interwoven and mixed to form a three-dimensional network structure.
[0010] Further preferably, the elastic colloid includes any one of soft non-flammable polyurethane colloid, silicone, and liquid silicone rubber.
[0011] Further preferably, the oriented nanofibers include a combination of halloysite nanotubes and goethite nanofibers, which are aligned under the action of a magnetic field.
[0012] Further preferably, the energy-absorbing gel is a gel body that uses a high specific surface area nanoporous material as a dispersed phase, is dissolved in a dispersed medium, and has a high energy absorption density of 60-250 joules / gram (J / g); the dispersed phase includes one or more of nano zeolite, nano silica, nano diatomaceous earth, and nano halloysite; the dispersed medium includes one of polyethylene glycol, methyl silicone oil, imidazole tetrafluoroborate, and pyridine tetrafluoroborate.
[0013] Further preferably, the dispersed phase uses a nano-dispersed phase with different adsorption ratios, and the nano-dispersed phase uses a compound of spherical nanoparticles and tubular nanotubes to achieve gradient energy absorption.
[0014] Preferably, the ceramic bulletproof layer is an N-layer staggered superposition structure, each layer is composed of M ceramic sheets arranged in an array, and a gap of 0.2-2 times the thickness of the ceramic sheet is reserved between adjacent ceramic sheets on the same plane. The ceramic sheets are bonded into a thin layer by pouring nano-energy-absorbing glue. The upper and lower layers of the thin layer are staggered and superimposed, and the upper and lower adjacent ceramic sheets are staggered and superimposed by 1 / 4 of the side length of the polygon to form a staggered bite structure, and the nano-energy-absorbing glue is poured and bonded to form an overall armor module.
[0015] Preferably, the ceramic sheet comprises one or more of alumina, silicon carbide, boron carbide, silicon nitride, aluminum nitride, titanium boride, zirconium boride ceramics, carbon aluminum alloy foam ceramics and ceramic foam materials.
[0016] Further preferably, the ceramic sheet is one of aluminum oxide, silicon carbide, boron carbide and silicon nitride.
[0017] Preferably, the ceramic sheet is hexagonal, and the corners of the hexagon form a canine bite; the size of the ceramic sheet is 10-20 mm in side length and 0.5-10 mm in single layer thickness.
[0018] A method for preparing a bionic ceramic armor module, characterized by comprising the following steps:
[0019] (I) Preparation of Nano Energy Absorbing Gel
[0020] (1) Material selection: The nano-dispersion body is selected from an inorganic composite system, one of a composite of nano-zeolite and halloysite nanotubes, a composite of nano-silicon dioxide and carbon nanotubes, and a composite of nano-diatomite and halloysite nanotubes; the dispersion medium is selected from an inorganic ionic liquid, including one of imidazole tetrafluoroborate and pyridine tetrafluoroborate;
[0021] (2) Material pretreatment: Select inorganic nano-dispersions with a particle size in the range of 20-300 nm, dry them in a constant temperature drying oven at 80-150°C for 36-48 hours to completely remove the bound water on the particle surface and make all energy-absorbing pores open;
[0022] (3) mixing the treated granular nanobody and tubular nanobody in a weight ratio of 7:3 evenly;
[0023] (4) firstly add the dispersion medium ionic liquid into the reaction kettle at a volume ratio of 50:100, raise the temperature to 40-80° C., slowly add the nanobody treated in step (3) under stirring, and stir at a high speed of 300 r / min for 2-4 hours until the system is evenly dispersed without agglomerated particles;
[0024] (5) placing the sol prepared in step (4) in a vacuum drying oven at 60-80° C. and drying for 10-20 hours to remove bubbles;
[0025] (II) Preparation of bonding colloid
[0026] (a) weighing nano-goethite, halloysite nanotubes, and a silane coupling agent in a weight ratio of 5:5:1, adding them to a planetary ball mill and grinding them for 2-4 hours to allow them to adsorb to each other to form a homogeneous magnetic body;
[0027] (b) drying the magnetic mixture prepared in step (a) in an oven at 100-120° C. for 5 hours;
[0028] (c) weighing a two-component resin glue, a resin component A and a curing component B, totaling 100 parts, with a weight ratio of component A to component B ranging from 100:2 to 100:50, weighing the magnetic mixture prepared in step (b) and the resin glue at a weight ratio of (5-20):100, first adding component A and mixing evenly;
[0029] (d) weighing 5-10% by weight of the nano energy absorbing gel and the component A containing the magnetic mixture prepared in step (c) and stirring evenly to prepare a component A mixture;
[0030] (e) different types of two-component resins, the weight ratio of component A to component B is 100:2 to 100:50, and the component A mixture prepared in step (d) is mixed with component B according to the above ratio during the adhesive application, and the nanofibers are oriented and distributed in a magnetic field environment, and cross-linked and cured into an elastic colloid;
[0031] (III) Preparation of ceramic armor modules
[0032] (I) spraying a layer of fluorine release agent evenly on the working platform;
[0033] (II) an automatic adhesive spreading machine evenly applies the adhesive colloid to a thickness of 0.1-3 mm, and uses a magnetic field to make the nanofibers in the colloid parallel and oriented and distributed in the colloid;
[0034] (III) using an array-type automatic chip mounter to neatly and orderly arrange the hexagonal ceramic pieces on the adhesive colloid according to the design requirements;
[0035] (IV) an automatic glue dispensing machine pours adhesive colloid to ensure that each gap is filled with colloid and maintains a thickness of 0.1-3 mm on parallel surfaces, and uses a magnetic field to make the nanofibers parallel and oriented in the colloid;
[0036] (V) Laying the second layer of ceramic sheets in a manner that the first layer of hexagonal ceramic sheets are offset by 1 / 4 of the side length, and curing the sheets in a magnetic field;
[0037] (VI) Repeat the above steps until the designed number of layers is reached, which is the finished ceramic armor module.
[0038] It is reported that limpet teeth are harder than diamonds and tougher than spider silk, making them the toughest materials known in the world. Their excellent mechanical properties come from their unique elemental composition, growth mechanism and framework structure, such as Figure 2 and Figure 3 As shown. Limpet teeth are mainly composed of goethite nanofibers, hydrated silica and flexible chitin. They are a perfect example of a combination of rigidity and flexibility. They can be deformed by pressures up to 6500 MPa (see Fig. 9 During the mineralization and crystallization process, goethite forms single fiber crystals that are orderly arranged in chitin, and countless nano-energy-absorbing particles develop in the crystals (see Fig.10 ), can quickly absorb and dissipate external impact, coupled with its orderly laminated macrostructure (see Fig.11 ), forming a synergistic mechanism of confrontation, absorption, transfer, and dissipation of external forces, resulting in its excellent mechanical properties.
[0039] According to the above technical solution, the beneficial effects of the present invention are as follows:
[0040] "Learning from nature" is the core of bionics. Only by imitating shape, quality and mechanism can we make breakthroughs in the field of bionic materials. The present invention imitates the constituent elements and structural characteristics of limpet teeth, which is known as the world's strongest material, to prepare a bulletproof ceramic armor module that is both rigid and flexible, thereby essentially solving the brittleness problem of the ceramic body and making it have the ability to resist multiple penetrations.
[0041] The present invention imitates the synergistic mechanism of limpet teeth against external forces. The structure adopts ceramic sheets in an orderly staggered stacking, which effectively transfers the external force and increases the pull-out force of the sheets. It is similar to the principle that 20 sheets of paper are easily pulled out when they are crossed, but 50 sheets of paper are impossible to pull out even if you use a lot of force (see Figure 8 ). The microscopic arrangement of the material structure in nature determines not only its form, but also its properties. Graphite and diamond are both carbon, but their hardness differs by 10,000 times due to their different structures. Graphite and graphene also differ by 10,000 times in toughness due to their different atomic arrangements. In terms of element combination, a combination of ceramic sheets and energy-absorbing colloids is used; in terms of formation mechanism, goethite nanofibers and halloysite nanotubes are arranged in an orderly manner in the energy-absorbing colloid, which greatly improves the toughness and strength of the energy-absorbing colloid. At the same time, nano energy-absorbing particles in the microstructure build energy absorption and transmission channels. The four effects work together to optimize the structural performance and fundamentally solve the brittleness of ceramic sheets. Its toughness is 18-50 times higher than that of single-element ceramic armor modules, its energy absorption density is increased by 6-60 times, and its weight is reduced by 50%-70%, which greatly improves its ability to resist multiple penetrations.
[0042] The invention can be programmed to design different numbers of layers, thicknesses, softness and hardness, weights, sizes and penetration resistance according to actual uses. The invention has the advantages of simple process, convenient manufacturing, convenient assembly, good module performance, green environmental protection, and large-scale and batch industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 , main structural diagram of ceramic armor module;
[0044] Figure 2 , Ceramic armor module plan;
[0045] Figure 3 , three-dimensional structure diagram of ceramic armor module;
[0046] Figure 4 , SEM image of nanofibers on the surface of the energy absorbing layer;
[0047] Figure 5 , SEM image of spherical nanoparticles in the energy absorption layer;
[0048] Figure 6 , SEM images of the composite of tubular nanotubes and spherical nanoparticles in the energy absorbing layer;
[0049] Figure 7 , SEM image of energy absorbing particles distribution inside the energy absorbing layer;
[0050] Figure 8 , diagram of the forces acting on laminated inserts;
[0051] Fig. 9 , SEM image of limpet teeth showing the fiber distribution on the surface of limpet teeth;
[0052] Fig.10 , SEM image of limpet teeth showing the ordered structure inside the limpet teeth;
[0053] Fig.11 , SEM image of limpet teeth showing the layered structure of limpet teeth. DETAILED DESCRIPTION
[0054] The following examples are provided to further illustrate the present invention rather than to limit the present invention.
[0055] The present invention is described below with reference to specific embodiments. It will be appreciated by those skilled in the art that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention in any way.
[0056] The experimental methods in the following examples are conventional methods unless otherwise specified. The medicinal materials, reagents, etc. used in the following examples are commercially available products unless otherwise specified.
[0057] A bionic ceramic armor module, characterized in that:
[0058] The bionic ceramic armor module includes N layers of staggered and superimposed ceramic bulletproof layers and nano-energy absorbing adhesive bonding layers. The ceramic bulletproof layer contains M ceramic sheets, which are arranged in an array. The ceramic sheets are tightly bonded by pouring nano-energy absorbing adhesive to form a single thin layer, and the single thin layers are staggered and superimposed in sequence; nano-energy absorbing adhesive is sprayed between the layers of the single thin layer to form a nano-energy absorbing adhesive bonding layer, and the ceramic bulletproof layer and the nano-energy absorbing adhesive bonding layer constitute a composite whole; N is an integer greater than 5; M is an integer greater than 20.
[0059] The nano energy-absorbing glue is composed of elastic colloid, oriented nanofibers and energy-absorbing gel; the three components are evenly interwoven and mixed to form a three-dimensional network structure. The nano energy-absorbing glue imitates the matrix structure of limpet teeth, and the nano energy-absorbing glue is tightly bonded to the ceramic sheet, playing the role of bonding, strengthening, toughening, energy absorption and buffering.
[0060] The elastic colloid includes any one of soft and non-flammable polyurethane colloid, silica gel and liquid silicone rubber.
[0061] The oriented nanofibers include a combination of halloysite nanotubes and goethite nanofibers, which are oriented under the action of a magnetic field. The oriented nanofibers mainly increase the toughness of the nano energy-absorbing adhesive.
[0062] The energy absorbing gel is a gel with a high specific surface area nanoporous material as a dispersed phase, dissolved in a dispersed medium, and having a high energy absorption density of 60-250 joules / gram (J / g); the dispersed phase includes one or more of nano zeolite, nano silicon dioxide, nano diatomaceous earth, and nano halloysite; the dispersed medium includes one of polyethylene glycol, methyl silicone oil, imidazole tetrafluoroborate, and pyridine tetrafluoroborate. The performance comparison of the energy absorbing gel of the present invention and commonly used energy absorbing materials is shown in Table 1.
[0063] Table 1. Comparison of energy absorbing material performance
[0064]
[0065] The dispersed phase is a compound of spherical nanoparticles and tubular nanotubes to achieve gradient energy absorption.
[0066] The energy absorption principle of the energy-absorbing gel is: the nanoporous material is dissolved in the gel body. Under normal circumstances, the functional fluid cannot enter the pores of the nanomaterial. Once an external force acts, the functional fluid will enter the pores and convert the external mechanical energy into the surplus surface tension and friction between the solid and liquid phases, absorbing a large amount of external energy and completing the energy conversion. When the external force is removed, the functional liquid flows out of the nanopores and returns to normal. This cycle repeats itself, efficiently completing the absorption, migration, conversion and buffering of external forces.
[0067] Among them, the ceramic bulletproof layer is an N-layer staggered superposition structure (N is generally an integer greater than 5), each layer is composed of M ceramic sheets arranged in an array (M is generally an integer greater than 20), and a gap of 0.2-2 times the thickness of the ceramic sheet is reserved between adjacent ceramic sheets on the same plane. The ceramic sheets are bonded into a thin layer by pouring nano-energy-absorbing glue. The upper and lower layers of the thin layer are staggered and superimposed, and the upper and lower adjacent ceramic sheets are staggered and superimposed with 1 / 4 of the side length of the polygon to form a staggered bite structure, which are poured with nano-energy-absorbing glue to form an overall armor module; the adjacent ceramic sheets on the same plane are reserved with gaps, the first purpose is to ensure that the bulletproof layer has a certain flexibility, and the second purpose is to achieve multi-directional displacement deformation to dissipate external force impact.
[0068] Wherein, the ceramic sheet comprises one or more of alumina, silicon carbide, boron carbide, silicon nitride, aluminum nitride, titanium boride, zirconium boride ceramics, carbon aluminum alloy foam ceramics and ceramic foam materials.
[0069] Among them, the ceramic sheet is preferably one of aluminum oxide, silicon carbide, boron carbide and silicon nitride.
[0070] In actual applications, the ceramic sheets can be selected according to different uses. The properties of commonly used bulletproof ceramics are shown in Table 2.
[0071] Table 2. Performance comparison of typical bulletproof ceramic materials
[0072]
[0073] The ceramic sheet is hexagonal, and the corners of the hexagon form a canine bite; the size of the ceramic sheet is 10-20 mm in side length and 0.5-10 mm in single layer thickness. The hexagon has the best mechanical performance and stability in the superposition system.
[0074] A method for preparing a bionic ceramic armor module, characterized by comprising the following steps:
[0075] (I) Preparation of energy absorbing gel
[0076] (1) Material selection: Based on environmental protection, economy and stability, the nano-dispersion selects an inorganic composite system, one of nano-zeolite and halloysite nanotube composite, nano-silicon dioxide and carbon nanotube composite, and nano-diatomite and halloysite nanotube composite. The dispersing medium selects an inorganic ionic liquid, including one of imidazole tetrafluoroborate and pyridine tetrafluoroborate;
[0077] (2) Material pretreatment: Select inorganic nano-dispersions with a particle size in the range of 20-300 nm, dry them in a constant temperature drying oven at 80-150°C for 36-48 hours to completely remove the bound water on the particle surface and make all energy-absorbing pores open;
[0078] (3) mixing the treated granular nanobody and tubular nanobody in a weight ratio of 7:3 evenly;
[0079] (4) firstly add the dispersion medium ionic liquid into the reaction kettle at a volume ratio of 50:100, raise the temperature to 40-80° C., slowly add the nanobody treated in step (3) under stirring, and stir at a high speed of 300 r / min for 2-4 hours until the system is evenly dispersed without agglomerated particles;
[0080] (5) placing the sol prepared in step (4) in a vacuum drying oven at 60-80° C. and drying for 10-20 hours to remove bubbles;
[0081] The distribution of energy-absorbing particles inside the energy-absorbing layer is as follows: Figure 5-Figure 7 shown.
[0082] (II) Preparation of elastic colloid
[0083] (a) weighing nano-goethite, halloysite nanotubes, and a silane coupling agent in a weight ratio of 5:5:1, adding them to a planetary ball mill and grinding them for 2-4 hours to allow them to adsorb to each other to form a homogeneous magnetic body;
[0084] (b) drying the magnetic mixture prepared in step (a) in an oven at 100-120° C. for 5 hours;
[0085] (c) weighing a two-component resin glue, a resin component A and a curing component B, totaling 100 parts, with a weight ratio of component A to component B ranging from 100:2 to 100:50, weighing the magnetic mixture prepared in step (b) and the resin glue at a weight ratio of (5-20):100, first adding component A and mixing evenly;
[0086] (d) weighing 5-10% by weight of the nano energy absorbing gel and the component A containing the magnetic mixture prepared in step (c) and stirring evenly to prepare a component A mixture;
[0087] (e) The weight ratio of component A to component B of different types of two-component resins is 100:2 to 100:50. When applying the glue, the component A mixture prepared in step (d) is mixed with the component B in proportion, and the nanofibers are oriented and distributed in a magnetic field environment, and cross-linked and cured into an elastic colloid;
[0088] (III) Preparation of ceramic armor modules
[0089] (I) spraying a layer of fluorine release agent evenly on the working platform;
[0090] (II) an automatic glue spreading machine evenly applies the elastic colloid to a thickness of 0.1-3 mm, and uses a magnetic field to make the nanofibers in the colloid parallel and oriented and distributed in the colloid;
[0091] (III) using an array-type automatic chip mounter to neatly and orderly arrange the hexagonal ceramic pieces on the elastic colloid according to the design requirements;
[0092] (IV) an automatic glue dispensing machine pours elastic colloid to ensure that each gap is filled with colloid and maintains a thickness of 0.1-3 mm on parallel surfaces, and uses a magnetic field to make the nanofibers parallel and oriented in the colloid;
[0093] (V) Laying the second layer of ceramic sheets in a manner that the first layer of hexagonal ceramic sheets are offset by 1 / 4 of the side length, and curing the sheets in a magnetic field;
[0094] (VI) Repeat the above steps until the designed number of layers is reached, which is the finished ceramic armor module.
[0095] The structure of the ceramic armor module is shown in the figure Figure 1 and Figure 3 As shown, the plan view is Figure 2 shown.
[0096] Embodiment 1: Lightweight ceramic armor module for individual soldiers
[0097] Individual armor protection is a powerful guarantee for the survival rate and combat effectiveness of soldiers on the battlefield. Lightweight, high strength, high toughness and flexibility are the development direction. According to the Chinese military bulletproof vest standard GJB4300-2002, which is divided into six levels (see Table 3), the ceramic armor module of the present invention can achieve different standard level requirements by changing the number of layers in the thickness direction.
[0098] Table 3. Performance classification table of Chinese military bulletproof vests
[0099]
[0100] The specific implementation is divided into three steps: preparation of nano energy-absorbing gel, preparation of elastic colloid, and preparation of ceramic composite module.
[0101] (I) Preparation of Nano Energy Absorbing Gel
[0102] (1) Material selection: Based on environmental protection, economy and stability, the nano-dispersion body is selected as an inorganic composite system, nano-silicon dioxide and carbon nanotube composite, and the dispersion medium is selected as an inorganic ionic liquid, pyridine tetrafluoroborate.
[0103] (2) Material pretreatment: Select nanoparticles with a particle size in the range of 20-300 nm and dry them in a constant temperature drying oven at 80-150°C for 36-48 hours to completely remove the bound water on the particle surface and make all energy-absorbing pores open.
[0104] (3) Take the treated nano-silicon dioxide and carbon nanotubes, mix them evenly in a weight ratio of 7:3.
[0105] (4) According to the ratio of the dispersion phase to the dispersion medium of 50:100 (volume ratio), the dispersion medium ionic liquid pyridinium tetrafluoroborate is first measured and added into the reaction kettle, and the temperature is raised to 40-80° C. under normal pressure, and the mixed nanobody treated in step (3) is slowly added under stirring, and the mixture is stirred at a high speed of 300 r / min for 2-4 hours until the system is evenly dispersed and there are no agglomerated particles.
[0106] (5) Place the gel prepared in step (4) in a vacuum drying oven at 60-80°C and dry it for 10-20 hours to remove bubbles.
[0107] (II) Preparation of elastic colloid (adhesive colloid)
[0108] (1) Nano-goethite, halloysite nanotubes, and a silane coupling agent are weighed in a weight ratio of 5:5:1 and added to a planetary ball mill for grinding for 2-4 hours to allow them to adsorb to each other to form a homogeneous magnetic body.
[0109] (2) The mixture prepared in step (1) is placed in an oven at 100-120° C. and dried for 5 hours.
[0110] (3) Weigh 100 parts of liquid silicone rubber component A and cross-linking curing component B, with a weight ratio of component A to component B of 100:2 or 100:4. Weigh the magnetic mixture and colloid prepared in step (2) in a mass ratio of (5-20):100, add them to the liquid silicone rubber component A and mix them evenly.
[0111] (4) Weigh the nano energy absorbing gel and the component A of the magnetic mixture prepared in step (3) in a mass ratio of (5-10)%, stir them evenly, and prepare a component A mixture.
[0112] (5) When applying the glue, the component A mixture prepared in step (4) is mixed with the component B at a weight ratio of component A to component B of 100:2 or 100:4, and the nanofibers are oriented and distributed in a magnetic field environment, and cross-linked and cured into an elastic colloid.
[0113] (III) Preparation of ceramic armor modules
[0114] (1) Spray a layer of fluorine release agent evenly on the work platform.
[0115] (2) The automatic glue spreading machine evenly spreads the adhesive colloid with a thickness of 0.5-1 mm, and uses a magnetic field to make the nanofibers in the colloid parallel and oriented and distributed in the colloid.
[0116] (3) Using an array-type automatic placement machine, hexagonal ceramic pieces with a side length of 2 mm and a thickness of 0.5-1 mm are neatly and orderly arranged on the adhesive colloid according to the design requirements and fixed.
[0117] (4) An automatic glue dispensing machine pours adhesive colloid to ensure that each gap is filled with colloid and maintains a thickness of 0.5-1 mm on the parallel surface. The magnetic field is used to make the nanofibers parallel and oriented in the colloid.
[0118] (5) The second layer of ceramic sheets is laid in a 1 / 4 offset manner according to the side length of the first layer of hexagonal ceramic sheets, and glue is applied and cured in a magnetic field environment.
[0119] (6) Repeat the above steps until the designed number of layers is reached, preferably 5-50 layers, which is the finished ceramic armor module. It is assembled with the constraint layer and the base plate to form a single-soldier bulletproof vest.
[0120] Embodiment 2: Ceramic armor modules for tanks and infantry fighting vehicles
[0121] With the advancement of science and technology, the battlefield environment has undergone tremendous changes, the degree of confrontation has become unprecedentedly fierce, and tanks and armored vehicles have begun to face more threats. At present, the armor used in the third-generation tanks is mainly composite armor, reactive armor and basin-shaft armor. Basin-shafts have radiation and have been banned in many countries. Reactive armor will cause accidental injuries to soldiers around the tank. my country has always abandoned it and has been committed to the research and development of high-performance composite armor. The ceramic armor module of the present invention adopts silicon carbide and nano-energy-absorbing adhesive laminated composite. In the absence of any constraint layer and base plate, the bending failure stress can reach 350-560Mpa, which is much greater than the 58Mpa requirement in GJB6447-2008, "Light Ceramic Composite Armor Specification", and the specific implementation is divided into three steps.
[0122] (I) Preparation of Nano Energy Absorbing Gel
[0123] (1) Material selection: Based on environmental protection, economy and stability, the nano-dispersion selects an inorganic composite system, nano-zeolite and halloysite nanotube composite, and the dispersion medium selects inorganic ionic liquid, imidazole tetrafluoroborate.
[0124] (2) Material pretreatment: Select inorganic nano-dispersions with a particle size in the range of 20-300 nm, dry them in a constant temperature drying oven at 80-150°C for 36-48 hours to completely remove the bound water on the particle surface and make all energy-absorbing pores open.
[0125] (3) The treated nano-zeolite and halloysite nanotubes are mixed uniformly in a weight ratio of 7:3.
[0126] (4) According to the ratio of the dispersed phase to the dispersed medium of 60:100 (volume ratio), the dispersing medium ionic liquid imidazolium tetrafluoroborate is first measured and added into the reaction kettle, the temperature is raised to 40-80° C., and the nanobody treated in step (3) is slowly added under stirring, and the mixture is stirred at a high speed of 300 r / min for 2-4 hours until the system is evenly dispersed and there are no agglomerated particles.
[0127] (5) Place the gel prepared in step (4) in a vacuum drying oven at 60-80°C and dry it for 10-20 hours to remove bubbles.
[0128] (II) Preparation of elastic colloid (adhesive colloid)
[0129] (1) Nano-goethite, halloysite nanotubes, and a silane coupling agent are weighed in a weight ratio of 5:5:1 and added to a planetary ball mill for grinding for 2-4 hours to allow them to adsorb to each other to form a homogeneous magnetic body.
[0130] (2) The mixture prepared in step (1) is placed in an oven at 100-120° C. and dried for 5 hours.
[0131] (3) Weigh 100 parts of liquid silicone rubber component A and cross-linking curing component B, with a weight ratio of component A to component B of 100:2 or 100:4. Weigh the magnetic mixture and colloid prepared in step (2) in a mass ratio of (5-20):100, add them to the liquid silicone rubber component A and mix them evenly.
[0132] (4) Weigh the nano energy absorbing gel and the component A of the magnetic mixture prepared in step (3) in a mass ratio of (5-10)%, stir them evenly, and prepare a component A mixture.
[0133] (5) When applying the glue, the weight ratio of component A to component B is 100:2 or 100:4, and the component A mixture prepared in step (4) is mixed with component B, and the nanofibers are oriented and distributed in a magnetic field environment, and cross-linked and cured into an elastic colloid.
[0134] (III) Preparation of ceramic armor modules
[0135] (1) Spray a layer of fluorine release agent evenly on the work platform.
[0136] (2) The automatic glue spreading machine evenly spreads the adhesive colloid with a thickness of 1-3 mm, and uses a magnetic field to make the nanofibers in the colloid parallel and oriented and distributed in the colloid.
[0137] (3) An array-type automatic chip mounter is used to arrange hexagonal ceramic sheets with a side length of 4 mm and a thickness of 5 mm neatly and orderly on the adhesive colloid according to the design requirements and fix them.
[0138] (4) An automatic glue dispensing machine pours adhesive colloid to ensure that each gap is filled with colloid and maintains a thickness of 1-3 mm on parallel surfaces. A magnetic field is used to make the nanofibers parallel and oriented in the colloid.
[0139] (5) The second layer of ceramic sheets is laid in a 1 / 4 offset manner according to the side length of the first layer of hexagonal ceramic sheets, and glue is applied and cured in a magnetic field environment.
[0140] (6) Repeat the above steps until the designed number of layers is reached, preferably 5-100 layers; this is the finished ceramic armor module, which is assembled with the constraint layer to form a tank armor.
[0141] Embodiment 3: Ceramic armor module for aircraft
[0142] Lightweighting of aircraft armor has always been a problem while ensuring high bulletproof performance. Boron carbide has the lowest density among ceramic materials and is the preferred bulletproof armor for aircraft. The present invention uses bionic technology to laminate boron carbide and nano energy-absorbing adhesive. Under the premise of ensuring protective performance, compared with single-element ceramics, the density is reduced by 70%, and the fracture toughness is increased by 20 times. It can be perfectly combined with the aircraft body through laminated spraying and paving technology to create a flying fortress.
[0143] The preparation method comprises the following steps:
[0144] (I) Preparation of Nano Energy Absorbing Gel
[0145] (1) Material selection: Based on the special bulletproof considerations of aircraft, the nano-dispersion selects an inorganic composite system, nano-silicon dioxide and carbon nanotube composite, and the dispersion medium selects inorganic ionic liquid and imidazole tetrafluoroborate.
[0146] (2) Material pretreatment: Select inorganic nano-dispersions with a particle size in the range of 20-300 nm, dry them in a constant temperature drying oven at 80-150°C for 36-48 hours to completely remove the bound water on the particle surface and make all energy-absorbing pores open.
[0147] (3) The treated nano-silicon dioxide and carbon nanotubes are mixed in a weight ratio of 7:3 and evenly mixed.
[0148] (4) According to the ratio of the dispersion phase to the dispersion medium of 50:100 (volume ratio), the dispersion medium ionic liquid imidazolium tetrafluoroborate is first measured and added into the reaction kettle, the temperature is raised to 40-80° C., and the nano-mixture treated in step (3) is slowly added under stirring, and the mixture is stirred at a high speed of 300 r / min for 2-4 hours until the system is evenly dispersed and there are no agglomerated particles.
[0149] (5) Place the sol prepared in step (4) in a vacuum drying oven at 60-80°C and dry it for 10-20 hours to remove bubbles.
[0150] (II) Preparation of elastic colloid (adhesive colloid)
[0151] (1) Nano-goethite, halloysite nanotubes, and a silane coupling agent are weighed in a weight ratio of 5:5:1 and added to a planetary ball mill for grinding for 2-4 hours to allow them to adsorb to each other to form a homogeneous magnetic body.
[0152] (2) The mixture prepared in step (1) is placed in an oven at 100-120° C. and dried for 5 hours.
[0153] (3) Weigh 100 parts of polyurethane resin component A and environmentally friendly curing agent TMP-TDI as component B, with a weight ratio of component A to component B of 5:1 or 4:1. Weigh the magnetic mixture prepared in step (2) and the polyurethane resin in a mass ratio of (15-20):100 (A+B), first add component A and mix evenly.
[0154] (4) Weigh the nano energy absorbing gel and the component A containing the magnetic mixture prepared in step (3) in a mass ratio of 8-10%, stir them evenly, and prepare a component A mixture.
[0155] (5) When applying the glue, the component A mixture prepared in step (4) is evenly mixed with the component B in a proportion (the weight ratio of component A: component B is 5:1 or 4:1) to complete the directional distribution of the nanofibers in a magnetic field environment, and then cross-linked and cured into an elastic colloid.
[0156] (III) Preparation of ceramic armor modules
[0157] (1) Spray a layer of fluorine release agent evenly on the work platform.
[0158] (2) The automatic glue spreading machine evenly spreads the adhesive colloid with a thickness of 0.2-0.3 mm, and uses a magnetic field to make the nanofibers in the colloid parallel and oriented and distributed in the colloid.
[0159] (3) An array-type automatic chip mounter is used to arrange hexagonal ceramic sheets with a side length of 2 mm and a thickness of 1 mm neatly and orderly on the adhesive colloid according to the design requirements.
[0160] (4) An automatic glue dispensing machine pours adhesive colloid to ensure that each gap is filled with colloid and maintains a thickness of 0.2-0.5 mm on the parallel surface. The magnetic field is used to make the nanofibers parallel and oriented in the colloid.
[0161] (5) The second layer of ceramic sheets is laid in a 1 / 4 offset manner according to the side length of the first layer of hexagonal ceramic sheets, and glue is applied and cured in a magnetic field environment.
[0162] (6) Repeat the above steps until the designed number of layers is reached. The number of layers is preferably 5-100 layers, which is the finished ceramic armor module. The module is assembled with the constraint layer and the back plate to form the aircraft bulletproof armor. Under certain conditions, the armor coating process can also be completed directly on the aircraft body by using a laminated spraying method.
[0163] The improved effects of the present invention are:
[0164] The present invention imitates the constituent elements and structural features of limpet teeth, which is known to be the toughest material known in the world, to prepare a bulletproof ceramic armor module that is both rigid and flexible, thereby essentially solving the brittleness problem of the ceramic body and enabling it to have multiple anti-penetration capabilities.
[0165] The present invention imitates the synergistic mechanism of limpet teeth against external forces. The structure adopts orderly staggered stacking of ceramic sheets, which effectively transfers the diffusion of external forces and increases the pull-out force of the sheets. Figure 8 ), it is very easy to pull out. It is the same principle as 50 pieces of paper crossed with each other. Even if you use a lot of force, you can't pull them out. The microscopic arrangement of the structure of natural materials not only determines their shape, but also their properties. Graphite and diamond are both carbon, but their hardness differs by 10,000 times due to their different structures. Graphite and graphene have different toughness due to different atomic arrangements. In terms of element combination, ceramic sheets and energy-absorbing colloids are used in a flexible and rigid combination; in terms of formation mechanism, goethite nanofibers and halloysite nanotubes are arranged in an orderly manner in the energy-absorbing colloid (see Figure 4 ), greatly improving the toughness and strength of the energy-absorbing colloid. At the same time, nano energy-absorbing particles in the microstructure build energy absorption and transmission channels. The four effects work together to optimize the structural performance and fundamentally solve the brittleness of ceramic sheets. Its toughness is 18-50 times higher than that of single-element ceramic armor modules, the energy absorption density is increased by 6-60 times, and the weight is reduced by 50%-70%, which greatly improves its multiple anti-penetration capabilities.
[0166] The invention can be programmed to design different numbers of layers, thicknesses, softness and hardness, weights, sizes and penetration resistance according to actual uses. The invention has the advantages of simple process, convenient manufacturing, convenient assembly, good module performance, green environmental protection, and large-scale and batch industrial production.
[0167] In summary, the above description of the specific implementation methods of the present invention is only a preferred embodiment of the present invention and does not limit the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention, as long as they do not deviate from the spirit of the present invention, are within the scope of the patent of the present invention.
Claims
1. A bionic ceramic armor module, characterized in that ; The bionic ceramic armor module includes N layers of staggered and superimposed ceramic bulletproof layers and nano-energy absorbing adhesive bonding layers. The ceramic bulletproof layer contains M ceramic sheets, which are arranged in an array. The ceramic sheets are tightly bonded by pouring nano-energy absorbing adhesive to form a single thin layer, and the single thin layers are staggered and superimposed in sequence; nano-energy absorbing adhesive is sprayed between the layers of the single thin layer to form a nano-energy absorbing adhesive bonding layer, and the ceramic bulletproof layer and the nano-energy absorbing adhesive bonding layer constitute a composite whole; N is an integer greater than 5; M is an integer greater than 20.
2. The bionic ceramic armor module according to claim 1, characterized in that: The nano energy-absorbing glue is composited by elastic colloid, oriented nanofibers and energy-absorbing gel; the three components are evenly interwoven and mixed to form a three-dimensional network structure.
3. The bionic ceramic armor module according to claim 2, characterized in that: The elastic colloid includes any one of soft and non-flammable polyurethane colloid, silica gel and liquid silicone rubber.
4. The bionic ceramic armor module according to claim 2, characterized in that: The oriented nanofibers include a combination of halloysite nanotubes and goethite nanofibers, and are oriented and arranged under the action of a magnetic field.
5. The bionic ceramic armor module according to claim 2, characterized in that: The energy-absorbing gel adopts a nanoporous material with a high specific surface area as a dispersed phase, is dissolved in a dispersed medium, and is a gel with a high energy absorption density of 60-250 joules / gram (J / g); the dispersed phase includes one or more of nano zeolite, nano silicon dioxide, nano diatomaceous earth, and nano halloysite; the dispersed medium includes one of polyethylene glycol, methyl silicone oil, imidazole tetrafluoroborate, and pyridine tetrafluoroborate.
6. The bionic ceramic armor module according to claim 5, characterized in that: The dispersed phase is a compound of spherical nanoparticles and tubular nanotubes to achieve gradient energy absorption.
7. The bionic ceramic armor module according to claim 1, characterized in that: The ceramic bulletproof layer is a staggered superposition structure of N layers, each layer is composed of M ceramic sheets arranged in an array, and a gap of 0.2-2 times the thickness of the ceramic sheets is reserved between adjacent ceramic sheets on the same plane. The ceramic sheets are bonded into thin single sheets by pouring nano energy-absorbing glue. The upper and lower layers of the thin single sheet are staggered and superimposed, and the upper and lower adjacent ceramic sheets are staggered and superimposed with 1 / 4 of the side length of the polygon left and right to form a staggered bite structure, which is poured with nano energy-absorbing glue to form an overall armor module.
8. The bionic ceramic armor module according to claim 1, characterized in that: The ceramic sheet comprises one or more of alumina, silicon carbide, boron carbide, silicon nitride, aluminum nitride, titanium boride, zirconium boride ceramics, carbon aluminum alloy foam ceramics and ceramic foam materials.
9. The bionic ceramic armor module according to claim 1, characterized in that: The ceramic sheet is hexagonal, and the corners of the hexagon form a canine bite; the size of the ceramic sheet is 10-20mm in side length and 0.5-10mm in single layer thickness.
10. A method for preparing a bionic ceramic armor module, characterized by: Follow these steps:
1. Preparation of Nano Energy Absorbing Gel (1) Material selection: The nanodispersion is an inorganic composite system, one of the composites of nano-zeolite and halloysite nanotubes, nano-silicon dioxide and carbon nanotubes, and nano-diatomaceous earth and halloysite nanotubes; the dispersion medium is an inorganic ionic liquid, including one of imidazole tetrafluoroborate and pyridine tetrafluoroborate; (2) Material pretreatment: Select inorganic nano-dispersions with a particle size in the range of 20-300 nm, dry them in a constant temperature drying oven at 80-150°C for 36-48 hours to completely remove the bound water on the particle surface and make all energy-absorbing pores open; (3) taking the treated granular nanobody and tubular nanobody and mixing them evenly in a weight ratio of 7:3; (4) According to the ratio of the volume of dispersion phase to dispersion medium of 50:100, firstly measure the dispersion medium ionic liquid and add it into the reactor, raise the temperature to 40-80°C, slowly add the nanoparticles treated in step (3) under stirring, and stir at a high speed of 300 r / min for 2-4 hours until the system is evenly dispersed and there are no agglomerated particles; (5) placing the sol prepared in step (4) in a vacuum drying oven at 60-80°C and drying for 10-20 hours to remove bubbles; (II) Preparation of bonding colloid (a) weighing nano-goethite, halloysite nanotubes, and a silane coupling agent in a weight ratio of 5:5:1, adding them to a planetary ball mill and grinding them for 2-4 hours to allow them to adsorb to each other to form a homogeneous magnetic body; (b) drying the magnetic mixture prepared in step (a) in an oven at 100-120° C. for 5 hours; (c) weighing a two-component resin adhesive, a resin component A and a curing component B, totaling 100 parts, with a weight ratio of component A to component B ranging from 100:2 to 100:50, weighing the magnetic mixture prepared in step (b) and the resin adhesive in a weight ratio of (5-20):100, first adding component A and mixing evenly; (d) weighing 5% to 10% by weight of the nano energy absorbing gel and the component A containing the magnetic mixture prepared in step (c) and stirring them evenly to prepare a component A mixture; (e) different types of two-component resins, component A: component B, with a weight ratio of 100:2 to 100:
50. When applying glue, the component A mixture prepared in step (d) is evenly mixed with component B according to the above ratio, and the nanofibers are oriented and distributed in a magnetic field environment, and cross-linked and cured into an elastic colloid; (III) Preparation of ceramic armor modules (I) Spray a layer of fluorine release agent evenly on the working platform; (II) The automatic glue spreading machine evenly spreads the adhesive colloid to a thickness of 0.1-3 mm, and uses a magnetic field to make the nanofibers in the colloid parallel and oriented and distributed in the colloid; (III) using an array-type automatic chip mounter to neatly and orderly arrange the hexagonal ceramic pieces on the adhesive colloid according to the design requirements; (IV) An automatic glue dispensing machine pours adhesive colloid to ensure that each gap is filled with colloid and maintains a thickness of 0.1-3 mm on parallel surfaces, and uses a magnetic field to make the nanofibers parallel and oriented in the colloid; (V) Laying the second layer of ceramic sheets at a 1 / 4 offset length of the first layer of hexagonal ceramic sheets, and curing the sheets in a magnetic field; (VI) Repeat the above steps until the designed number of layers is reached, which is the finished ceramic armor module.
Citation Information
Patent Citations
Fiber / ceramic / metal composite material bulletproof plate and manufacturing method thereof
CN103727842A
Ceramic composite material bullet-proof chest board and preparation method thereof
CN104949581A
Gradient ceramic matrix composite material and preparation method thereof
CN114853478A
Composite bulletproof plugboard and preparation method thereof
CN114963874A
Composite armor of bionic structure and preparation method of composite armor
CN117073463A
Cited By
Composite protection device and preparation method and application thereof
CN119803190A